A novel endophytic fungus strain of Cladosporium: its identification, genomic analysis, and effects on plant growth - Yang, Nan; Zhang, Wenbin; Wang, Dan; Cao, Dingding; Cao, Yanyu; He, Weihong; Lin, Ziting; Chen, Xiaofeng; Ye, Guiping; Chen, Zhiming; Chen, Jianjun; Wei, Xiangying (Frontiers in Microbiology, 2023)
Introduction: Endophytic microorganisms are bacteria or fungi that inhabit plant internal tissues contributing to various biological processes of plants. Some endophytic microbes can promote plant growth, which are known as plant growth-promoting endophytes (PGPEs). There has been an increasing interest in isolation and identification of PGPEs for sustainable production of crops. This study was undertaken to isolate PGPEs from roots of a halophytic species Sesuvium portulacastrum L. and elucidate potential mechanisms underlying the plant growth promoting effect. Methods: Surface-disinfected seeds of S. portulacastrum were germinated on an in vitro culture medium, and roots of some germinated seedlings were contaminated by bacteria and fungi. From the contamination, an endophytic fungus called BF-F (a fungal strain isolated from bacterial and fungal contamination) was isolated and identified. The genome of BF-F strain was sequenced, its genome structure and function were analyzed using various bioinformatics software. Additionally, the effect of BF-F on plant growth promotion were investigated by gene cluster analyses. Results: Based on the sequence homology (99%) and phylogenetic analysis, BF-F is likely a new Cladosporium angulosum strain or possibly a new Cladosporium species that is most homologous to C. angulosum. The BF-F significantly promoted the growth of dicot S. portulacastrum and Arabidopsis as well as monocot rice. Whole genome analysis revealed that the BF-F genome has 29,444,740 bp in size with 6,426 annotated genes, including gene clusters associated with the tryptophan synthesis and metabolism pathway, sterol synthesis pathway, and nitrogen metabolism pathway. BF-F produced indole-3-acetic acid (IAA) and also induced the expression of plant N uptake related genes. Discussion: Our results suggest that BF-F is a novel strain of Cladosporium and has potential to be a microbial fertilizer for sustainable production of crop plants. The resulting genomic information will facilitate further investigation of its genetic evolution and its function, particularly mechanisms underlying plant growth promotion.